Evaluation of Solanum lasiocarpum Fruit Extract on Blood Glucose, Hematological Parameters, and Liver and Kidney Function in Alloxan-induced Diabetic Rats - Syukriah; Nurlian Augustin Ningrum; Siti Amira (Faculty of Medicine, Universitas Mataram, 2026)
Hyperglycemia is an increase in blood glucose levels that leads to diabetes mellitus. Diabetes mellitus caused by insulin resistance and impaired insulin secretion. Eggplant (Solanum lasiocarpum) is an herbal plant used as a traditional remedy for diabetes mellitus. This study aims to determine the effect of Eggplant fruit extract (S. lasiocarpum) on blood glucose, blood profile, SGPT, SGOT, creatinine, and ureum levels in diabetic rats. This study used a completely randomized design with six groups (G1: normal control, G2: diabetes control, G3: metformin control, G4: extract dose 200 mg/kg BW; G5: extract dose 300 mg/kg BW; and G6: extract dose 400 mg/kg BW. Measurement of SGPT, SGOT, Urea, and Creatinine levels using a spectrophotometer. Data analysis uses one-way ANOVA and Duncan at a significance level of 0.05. Statistical analysis revealed a significant difference (p<0.05) between the control group and extract therapy in blood glucose, blood profile tests, SGPT, SGOT, creatinine, and urem. The optimal dose of S. lasiocarpum fruit extract to reduce the effects caused by diabetes was 400 mg/kg BW.